2011
DOI: 10.1007/s10152-011-0265-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and reproductive biology of the little cuttlefish Sepiola atlantica (Cephalopoda: Sepiolidae) around Anglesey, North Wales

Abstract: Sepiola atlantica were captured in seine nets at twelve locations around the coast of Anglesey, UK. Animals were most abundant on the very sheltered shore of Y Foryd Bay and the wave-exposed shore of Traeth Penrhos, and these two locations were further sampled seasonally to examine the seasonal occurrence, population structure and reproductive biology of S. atlantica. Sepiola atlantica (5-28 mm dorsal mantle length (DML)) migrated inshore seasonally and Wrst appeared in July where they attained peak abundances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Implantation area of spermatangia is an enlarged area of distal oviduct (Rodrigues et al, 2012). According to Jones and Richardson (2011) species Sepiola atlantica contains 22 sprematangia in its bursa copulatrix, and by Rodrigues et al (2011) it was reported that implanted sprematangia in the bursa copulatrix could survive up to 104 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Implantation area of spermatangia is an enlarged area of distal oviduct (Rodrigues et al, 2012). According to Jones and Richardson (2011) species Sepiola atlantica contains 22 sprematangia in its bursa copulatrix, and by Rodrigues et al (2011) it was reported that implanted sprematangia in the bursa copulatrix could survive up to 104 days.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatangia are implanted in bursa copulatrix, which is located in the genital opening of females, or into the wrinkled area (Jones and Richardson, 2011), which is called seminal receptacle. Implantation area of spermatangia is an enlarged area of distal oviduct (Rodrigues et al, 2012).…”
Section: Discussionmentioning
confidence: 99%